The Performance of a drying machine utilizing an air dehumidification process for marungga leaves and identification of marungga flour - Djamila, Siti; Iswahyono, Iswahyono; Wibisono, Yossi; Hermanuadi, Didiek; Supriyono, Supriyono; Bahariawan, Amal; Faizin, Muhammad Alif; Sakdiya, Siti Arifatu (P3M Politeknik Negeri Jember, 2024)
Marungga leaves have the potential to be a source of antioxidants, minerals, and carbohydrates. These leaves can be processed into flour for further processing into various products. Marungga leaves must be dried before they can be processed into flour. They are heat-sensitive, so some of their nutritional content will be degraded if dried at high temperatures. A dehumidification system dryer was designed and built to produce low temperature and humidity to overcome the problem of high-temperature drying. The purpose of this study was to evaluate the performance of the dehumidification dryer and to assess the quality of dried Marungga flour. Drying was carried out under normal working conditions for 8 hours, with air temperature and humidity monitored at 20-minute intervals. The dried Marungga leaves were milled into flour and analyzed for physicochemical properties. The test results yielded the following data: air flow rate 0.109 kg/s, drying temperature 33.5°C, relative humidity 54.7%, drying rate 0.732 kg H2O/hour, specific humidity drop 0.01703 kg H2O/kgda, Carnot COP 6.8, actual COP 4.2, efficiency 61.8 %, SMER 0.055 kg/kWh. The Marungga flour produced had a moisture content 6.4%, protein 36.86%, antioxidants 58.765%, vitamin C 50.338%, and green color (a = -12.75) meets SNI 9228: 2023